2011
DOI: 10.1523/jneurosci.4540-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofcis-Elements and Transcription Factors Regulating Neuronal Activity-Dependent Transcription of HumanBDNFGene

Abstract: Brain-derived neurotrophic factor (BDNF) is an important mediator of activity-dependent functions of the nervous system and its expression is dysregulated in several neuropsychiatric disorders. Regulation of rodent BDNF neuronal activity-dependent transcription has been relatively well characterized. Here, we have studied regulation of human BDNF (hBDNF) transcription by membrane depolarization of cultured mouse or rat primary cortical neurons expressing hBDNF gene or transfected with hBDNF promoter constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
228
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(247 citation statements)
references
References 49 publications
(93 reference statements)
9
228
0
1
Order By: Relevance
“…Because, as mentioned above, Npas4 can regulate the expression of Bdnf exon IV, our data suggest that chronic duloxetine may restore the correct expression of Bdnf in SERT À/À rats via modulation of the transcription factor. Moreover, we show that the expression of Arnt2, another transcription factor that cooperate with Npas4 in the regulation of Bdnf exon IV (Pruunsild et al, 2011) is also significantly reduced in SERT À/À rats, although its expression can be restored by duloxetine treatment in the prefrontal cortex, but not in the hippocampus.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Because, as mentioned above, Npas4 can regulate the expression of Bdnf exon IV, our data suggest that chronic duloxetine may restore the correct expression of Bdnf in SERT À/À rats via modulation of the transcription factor. Moreover, we show that the expression of Arnt2, another transcription factor that cooperate with Npas4 in the regulation of Bdnf exon IV (Pruunsild et al, 2011) is also significantly reduced in SERT À/À rats, although its expression can be restored by duloxetine treatment in the prefrontal cortex, but not in the hippocampus.…”
Section: Discussionmentioning
confidence: 82%
“…It is interesting to note that Npas4 is a transcription factor associated with promoters I and IV of the Bdnf gene (Pruunsild et al, 2011), suggesting that it may directly regulate activity-dependent expression of the neurotrophin . Interestingly, we have previously demonstrated that SERT À/À rats have reduced Bdnf expression in the hippocampus and prefrontal cortex, and that this occurs through the modulation of different Bdnf transcripts, including exon I and exon IV .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown how the interaction between all these factors is complex and likely involves BDNF, the demethylating protein GADD45B, and hypoxia-related mechanisms. For example, binding of CREB 51 and GADD45B 52 in the BDNF region upstream of the rs6265 SNP has been detected. Moreover, BHLHB2 and GADD45B are regulated by hypoxia, since they have a highstringency HIF1 binding site, 53,54 and BHLHB2 represses expression of MITF, 53 a TF stimulating HIF1a expression.…”
Section: Relationship Between Rs6265 Genotype and Dna-protein Bindingmentioning
confidence: 99%